Answer:
Step-by-step explanation:
3x² - 33x + 54 = 0
Divide the whole equation by 3
x²- 11x + 18 = 0
Sum = -11
Product = 18
Factors = -9 , -2 { - 9 + (-2) = -11 ; (-9) *(-2) = 18}
x² - 2x - 9x + -9 * -2 = 0
x(x - 2) - 9(x - 2) = 0
(x-2)(x-9) = 0
x - 2 = 0 ; x - 9 = 0
x = 2 ;x = 9
Lesser x = 2
greater x = 9
Answer:
lesser x = 2
greater x = 9
Step-by-step explanation:
3x² - 33x + 54 = 0
Divide both side of the equation by 3
x² - 11 x + 18 = 0
x² - 2x - 9x + 18 = 0
x ( x - 2 ) - 9 ( x - 2 ) = 0
( x - 9 ) ( x - 2) = 0
x - 2= 0 ; x - 9 = 0
solve for x
x = 2 ; x = 9
lesser x = 2
greater x = 9